Linkage map construction and QTL identification for yield related traits of rice (Oryza sativa L.) - Tun, Khin Swe Hlaing; Htun, Than Myint; Htwe, Nyo Mar; Aye, Myint; Talukdar, Akshay; Thein, Min San (Research and Social Study Institute, 2023)
The study was undertaken to construct a linkage map and to identify the QTLs for heading date, plant height, and culm strength using a F2 population derived from Ayeyarmin/IR 64, two varieties distinctly different in heading date and plant height. A total of 233 F2 individuals were genotyped using 70 SSR primers, and phenotypic data were collected for heading date, plant height and culm strength traits. Fifty-four out of 70 marker loci were mapped across twelve rice chromosomes spanning a total map length of 1592.30 cM with an average distance of 29.49 cM between adjacent marker loci using MAPMAKER/EXP 3. Composite interval mapping for QTL analysis was conducted with 1000 permutation time at 0.05 probability level using WinQTL Cartographer version 2.5. One major QTL for heading date was mapped between marker RM204 and RM50 on chromosome 6. One major QTL for culm strength was mapped between marker RM1003-RM5931, and two major QTLs for plant height were mapped between RM84-RM1003 and RM1003-RM5931 on chromosome 1. The molecular markers linked to the major QTLs could be potentially used in marker-assisted selection for the rainfed rice improvement breeding program.